SPECIAL RETIREMENT UNDER OWN SOCIAL SECURITY SCHEMES UNDER THE VIEWING OF BINDING SUMMARY Nº 33 (Desenvolvimento em Questão, 2020)
Social security is a fundamental right guaranteed by the Federal Constitution, so that there is a special statutory retirement provision for policyholders who work in conditions that harm health and physical integrity. In view of the government's legislative law issuing a complementary law that regulates special retirement, public servants covered by public regimes accept admission to the Supreme Federal Court in order to guarantee the right to enjoy special retirement. In this sense, the objective of this study was to analyze the current panorama of special retirement within the scope of single schemes. To this end, a bibliographic study was carried out, using a deductive and exploratory method, through qualitative research. It is a documentary research, which analyzes, in addition to books and articles, laws and regulations. As a result, it can be identified that special retirement was resolved through the Judiciary and not the Legislative and Executive Branch, which would be the correct path. Standardization, through the binding summary, urgently resolved the legislative majority and gave civil servants or the right to enjoy retirement. The binding summary guaranteed the copyright of all policyholders, but did not consider the financial and operational issues of the single schemes, associated with the principle of consideration.
Keywords: Federal constitution. Social welfare regime. Civil servant. Special retirement. Binding docket 33.